The Synthesis Followed by Spectral and Calorimetric Evaluation of Stability of Human Milk Fat Substitutes Obtained from Thistle Milk and Lard - Joanna Bryś; lnês Filipa Vaz Flores; Agata Górska; Ewa Ostrowska–Ligęza; Andrzej Bryś; Tomasz Niemiec; Piotr Koczoń (International Journal of Analytical Chemistry)
The central point of current investigations was the first time ever synthesis of modern substitutes of human milk fat followed by versatile evaluation of their oxidative properties. The enzymatic interesterification conducted at 70°C for 2, 4, and 6 hours, respectively, with milk thistle oil and lard blend as starting reactants was catalyzed by 1,3-specific lipase Lipozyme RM IM, obtained from Rhizomucor miehei. Pressure Differential Scanning Calorimetry (PDSC) and Fourier Transform Infrared Spectroscopy (FT-IR) were applied to evaluate quality of products formed. Although PDSC curves showed lower oxidative stability of newly synthesized fats as compared to both starting materials separately, they can be considered adequate substitutes of human fat milk fat, as distribution of fatty acids in triacylglycerol molecules of substitutes obtained is much alike human milk fat itself, as resulted from analysis of GC data collected. Obvious changes in chemical structure of fats occurring during interesterification resulted in specific alterations in IR spectra of processed materials. Spectral data accompanied by PLS technique were successfully used for accurate determination of oxidative stability of new fats through indirect procedure, i.e., IR-PDSC-reference analysis of induction time. Additionally IR data exclusively, i.e., without any reference data, occurred powerfully in discrimination of human fat milk substitutes obtained.